Mutual functional dependence of cyclase-associated protein 1 (CAP1) and cofilin1 in neuronal actin dynamics and growth cone function. (July 2021) - Schneider, Felix; Duong, Thuy-An; Metz, Isabell; Winkelmeier, Jannik; Hübner, Christian A.; Endesfelder, Ulrike; Rust, Marco B.
Highlights: CAP1 is an important regulator of F-actin organization and dynamics in growth cones. hippocampal neurons lacking CAP1 display defects in neuron differentiation as well as growth cone function and motility. Neuron connectivity is compromised in brains from CAP1 mutant mice. Neurons lacking the key actin regulator cofilin1 display growth cone defects similar to neurons lacking CAP1. Rescue experiments in mutant neurons reveal functional interdependence of CAP1 and cofilin1 in growth cones. Abstract: Neuron connectivity depends on growth cones that navigate axons through the developing brain. Growth cones protrude and retract actin-rich structures to sense guidance cues. These cues control local actin dynamics and steer growth cones towards attractants and away from repellents, thereby directing axon outgrowth. Hence, actin binding proteins (ABPs) moved into the focus as critical regulators of neuron connectivity. We found cyclase-associated protein 1 (CAP1), an ABP with unknown brain function, abundant in growth cones. Super-resolution microscopy and live cell imaging combined with pharmacological approaches on hippocampal neurons from gene-targeted mice revealed a crucial role for CAP1 in actin dynamics that is critical for growth cone morphology and function. Growth cone defects in CAP1 knockout (KO) neurons compromised neuron differentiation and was associated with impaired neuron connectivity in CAP1-KO brains. Mechanistically, by rescue experiments in double KO neurons lacking CAP1 and the key actin regulator cofilin1, we demonstrated that CAP1 was essential for cofilin1 function in growth cone actin dynamics and morphology and vice versa . Together, we identified CAP1 as a novel actin regulator in growth cones that was relevant for neuron connectivity, and we demonstrated functional interdependence of CAP1 and cofilin1 in neuronal actin dynamics and growth cone function.